PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE AUDIO VISUAL TERHADAP PENGETAHUAN PERTOLONGAN PERTAMA PADA SISWA YANG MENGALAMI SINKOP - Friska Ernita Sitorus; Rostiodertina Girsang; Zuliawati Zuliawati; Wardani Nasution (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Fainting usually occurs suddenly, syncope can be caused due to too long in the hot sun. Syncope can also be caused by external diseases (weather, wind, heat) or emotional or shocking diseases. The purpose of this study was to determine the effect of health education by the audiovisual method on first aid knowledge in students who experienced syncope in Delitua 1 Public High School. This research method is Pre Experimental with the research design used by One Group Pre Test Post Test. The sampling technique uses Systematic Random Sampling with a sample of 65 students. The results of the study using the Wilcoxon test (The Signed Rank Test) obtained a significant value of 0.013 <0.05. The conclusions of the results of this study indicate that there is an effect of health education by the audiovisual method on first aid knowledge in students who experience syncope in Delitua 1 Public High School.